PERAN GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MATA PELAJARAN PAI - Achadah, Alif; Mulyati, Eka Desi (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2020)
Education is very important in the development of a nation. With education the nation can become more advanced with the presence of a younger generation who is able to answer the challenges of the times. But in education it is not only aimed at increasing one's knowledge, but education also aims to make someone's behavior and morals better. So that in the application of learning in schools, the role of Islamic Education teachers is very important in to increase student motivation. In this study, taking the problem of "The Role of Islamic Education Teachers in Increasing Student Motivation in Islamic Education Subjects in SMP PGRI Kromengan Malang Regency" which is based on the phenomenon of PAI teachers who have a role in building student motivation. The research focus includes: 1) How is the student's learning motivation in Islamic Education learning? 2) What is the role of Islamic Education teachers in increasing student learning motivation in Islamic Education subjects at SMP PGRI Kromengan? 3) What are the obstacles and solutions of Islamic Education teachers in increasing learning motivation students in the PAI subject at SMP PGRI Kromengan?Â Keywords: Islamic Education Teacher, Motivation to LearnÂ AbstrakPendidikan merupakan hal yang sangat penting dalam perkembangan suatu bangsa. Dengan pendidikan pula bangsa dapat menjadi lebih maju dengan adanya generasi muda yang mampu menjawab tantangan perkembangan zaman. Tetapi dalam pendidikan bukan hanya bertujuan untuk meningkatkan pengetahuan seseorang tetapi pendidikan juga bertujuan untuk menjadikan perilaku dan akhlak seseorang menjadi lebih baik. Sehingga dalam penerapan pembelajaran disekolah, peran guru PAI sangatlah penting dalam upaya meningkatkan motivasi belajar siswa. Dalam penelitian ini mengambil permasalahan tentang â€œPeran Guru PAI Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran PAI di SMP PGRI Kromengan Kabupaten Malangâ€ yang hal tersebut dilatar belakangi karena adanya fenomena dari guru PAI yang mempunyai andil dalam membangun motivasi peserta didik. Adapun fokus penelitian meliputi : 1)Â  Bagaimana motivasi belajar siswa dalam pembelajaran PAI?, 2) Bagaimana peran guru PAI dalam meningkatkan motivasi belajar siswa pada mata pelajaran PAI di SMP PGRI Kromengan?, 3) Apa saja kendala dan solusi guru PAI dalam meningkatkan motivasi belajar siswa pada mata pelajaran PAI di SMP PGRI Kromengan?Â Kata Kunci: Guru PAI, Motivasi belajar